Structural studies on lead-cadmium fluoride solid solutions - Silva, MAP; Messaddeq, Younes [UNESP]; Briois, V; Poulain, M.; Villain, F.; Ribeiro, SJL (Elsevier B.V., 2002)
(1-x)PbF2-(x)CdF2 solid solutions (with 0.1 less than or equal to x less than or equal to 0.5) were obtained by hyper-quenching the melt. Structural characteristics have been studied by X-ray diffraction (XRD) and extended X-ray absorption fine structure (EXAFS). A cubic solid solution was obtained in which the lattice parameter decreases with increasing CdF2 content. High anionic disorder was evidenced from EXAFS investigations, whereas cations remain in the FCC arrangement. Pb L-3-edge EXAFS results illustrate clearly the occurrence of CdxPb1-xF2 mixed crystals by the introduction of Cd atoms in the second Pb coordination shell. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: X-ray absorption spectroscopy; solid solutions; lead-cadmium fluoride